Weight loss surgery for non-morbidly obese populations with type 2 diabetes: is this an acceptable option for patients?. Issue 3 (5th June 2013) - Summers, Rachael H.; Elsey, Helen; Moore, Michael; Byrne, Christopher; Byrne, James; Welbourn, Richard; Roderick, Paul
<x content-type="archive" xml:space="preserve">Abstract</x> Aim To explore the views of non-morbidly obese people (BMI 30–40 kg/m2) with type 2 diabetes regarding: (a) the acceptability of bariatric surgery (BS) as a treatment for type 2 diabetes, and (b) willingness to participate in randomised controlled trials comparing BS versus non-surgical intervention. Background Despite weight management being a key therapeutic goal in type 2 diabetes, achieving and sustaining weight loss is problematic. BS is an effective treatment for people with morbid obesity and type 2 diabetes; it is less certain whether non-morbidly obese patients (BMI 30–39.9 kg/m2) with type 2 diabetes benefit from this treatment and whether this approach would be cost-effective. Before evaluating this issue by randomised trials, it is important to understand whether BS and such research are acceptable to this population. Methods Non-morbidly obese people with type 2 diabetes were purposively sampled from primary care and invited to participate in semi-structured interviews. Interviews explored participants' thoughts surrounding their diabetes and weight, the acceptability of BS and the willingness to participate in BS research. Data were analysed using Framework Analysis.